A Transfer Pricing System Based on Opportunity Cost. - Onsi, Mohamed (The Accounting Review, 1970)
The article presents information on the economic foundation of transfer pricing system. When there is a market price for intermediate goods, they are transferred according to such a price, assuming that the goods transferred are produced in a competitive market where the supplying center cannot influence the sales price in the open market by its own output decision. Pricing intermediate goods according to market price has the advantage of motivating the supplying center to reduce its cost as much as possible and emphasize innovation and research and development, since it will be to its advantage. Inventory level and asks for an explanation if it exceeds a certain level. Another solution is that the buying division commits itself to acquire a certain volume. These methods are partial solutions to the problem. Approximating marginal costs, to price transfer goods has several limitations since this approach ignores several strategic factors. Arriving at an optimal solution based on opportunity costs from the company's point of view, accepted by profit centers, is feasible.